2007
DOI: 10.1039/b615357g
|View full text |Cite
|
Sign up to set email alerts
|

Green synthesis of silver nanoparticles using Capsicum annuum L. extract

Abstract: Silver nanoparticles (NPs) were rapidly synthesized by treating silver ions with a Capsicum annuum L. extract. The reaction process was simple and convenient to handle, and was monitored using ultraviolet-visible spectroscopy (UV-vis). The effect of Capsicum annuum L. proteins on the formation of silver NPs was investigated using X-ray photoemission spectroscopy (XPS), electrochemical measurements, Fourier-transform infrared spectroscopy (FTIR) and differential spectrum techniques. The morphology and crystalli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
428
1
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 916 publications
(455 citation statements)
references
References 41 publications
22
428
1
4
Order By: Relevance
“…The results suggested that the capping ligand of the silver NPs may be an aromatic compound. It was reported that the extract of unicellular green algae C. vulgaris was used to synthesize single-crystalline silver nanoplates at room temperature (Xie et al, 2007). Proteins in the extract provide dual function of Ag+ reduction and shape-control in the synthesis of the silver NPs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results suggested that the capping ligand of the silver NPs may be an aromatic compound. It was reported that the extract of unicellular green algae C. vulgaris was used to synthesize single-crystalline silver nanoplates at room temperature (Xie et al, 2007). Proteins in the extract provide dual function of Ag+ reduction and shape-control in the synthesis of the silver NPs.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that extracts from microbes act both as reducing and capping agents in metal synthesis of nanoparticles. Reduction of metal ions by combinations of biomolecules such as enzymes or proteins, amino acids, polysaccharides, and vitamins (Collera-Zuniga et al, 2005) which may be used as reductants to react with silver ions, leading to silver NPs synthesis in solutions (Li et al, 2007) is environmentally benign, yet chemically complex. The overall suggestions are that proteins and polysaccharides were involved in the reduction of AgNO 3 to form silver NPs and the capping agents may be the aromatic compounds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6). FTIR spectra data is commonly used for identifying biomolecule responsible for the reduction of Ag + ions and the capping of the bioreduced Ag-NPs (Li et al, 2007;Song et al, 2009;Travan et al, 2009;Vanmathiselvi and Sivakumar, 2012). FTIR spectral peaks of Ag-NPs were strong and of crude were weak in Hedophyllum sessile (Fig.…”
Section: Characterization Of Ag-nps By Uv Ftir and Xrd Studymentioning
confidence: 99%
“…Nanochemistry mainly focuses on the synthesis of various metal nanoparticles like gold, silver, zinc, platinum [2][3][4][5], etc., due to its unique properties, which opens a new venue for the production of nanodevices, therapeutics, drugs, etc., in the field of nanomedicine and nanobiotechnology [6][7][8][9][10][11][12]. Gold nanoparticles have diverse applications in cancer treatment, electrochemical sensors, biosensors, gene and drug delivery, catalysis, etc., [13,14].…”
Section: Introductionmentioning
confidence: 99%